Atmospheric and Oceanographic Signatures in the Ice Shelf Channel Morphology of Roi Baudouin Ice Shelf, East Antarctica, Inferred From Radar Data. Issue 7 (9th July 2020) - Drews, R.; Schannwell, C.; Ehlers, T. A.; Gladstone, R.; Pattyn, F.; Matsuoka, K.
Abstract : Ice shelves around Antarctica can provide back stress for outlet glaciers and control ice sheet mass loss. They often contain narrow bands of thin ice termed ice shelf channels. Ice shelf channel morphology can be interpreted through surface depressions and exhibits junctions and deflections from flowlines. Using ice flow modeling and radar, we investigate ice shelf channels in the Roi Baudouin Ice Shelf. These are aligned obliquely to the prevailing easterly winds. In the shallow radar stratigraphy, syncline and anticline stacks occur beneath the upwind and downwind side, respectively. The structures are horizontally and vertically coherent, except near an ice shelf channel junction where patterns change structurally with depth. Deeper layers truncate near basal incisions. Using ice flow modeling, we show that the stratigraphy is ∼9 times more sensitive to atmospheric variability than to oceanic variability. This is due to the continual adjustment toward flotation. We propose that syncline‐anticline pairs in the shallow stratigraphy are caused by preferential snow deposition on the windward side and wind erosion at the downwind side. This drives downwind deflection of ice shelf channels of several meters per year. The depth variable structures indicate formation of an ice shelf channel junction by basal melting. We conclude that many ice shelf channels are seeded at the grounding line. Their morphology farther seaward is shaped on different length scales by ice dynamics, the ocean, and the atmosphere. These processes act on finer (subkilometer) scales than are captured by most ice, atmosphere, and ocean models, yet the dynamics of ice shelf channels may have broader implications for ice shelf stability. Plain Language Summary: Ice flows from Antarctica's interior toward the coast. At the contact point between ice and ocean, the ice becomes afloat and forms fast‐flowing ice shelves. Snowfall continuously accumulates at the ice shelf surface, and at the ice shelf bottom the relatively warm ocean water can melt ice from below. Ice shelves sometimes exhibit a network of surface depressions resembling a river network. At the base, the depressions are accompanied by large incisions termed ice shelf channels. Using radar as a tool for echolocation, we investigate how the shape of this network is formed. We find that snow preferentially collects in the upwind side of the surface depressions. This makes ice shelf channels move to the downwind side. We also find that ice shelf channels can form junctions through localized ocean melting. This is important because it helps us to better understand how the Antarctic ice sheet interacts with the surrounding ocean. Key Points: The radar stratigraphy in ice shelves is 9 times more sensitive to variability in snow deposition than to variability in basal melting Some ice shelf channels at Roi Baudouin Ice Shelf deflect from flowlines; the radar stratigraphy reflects related processes Variable snow deposition causes slow deflection, and basal melting can form ice shelf channel junctions far from the grounding line